DEKONSTRUKSI WAKAF MASJID MELALUI MODEL POAC UNTUK PEMBERDAYAAN EKONOMI MASYARAKAT BERBASIS PRODUKTIVITAS - Arum Fitri Lestari Arum (Indonesia Journal of Zakat and Waqf, 2024)
Most mosque waqf in Indonesia is utilized for worship purposes, such as the construction of mosques and prayer rooms. However, its role in community economic empowerment remains limited. This study aims to develop a productive waqf management model based on the POAC framework (Planning, Organizing, Actuating, Controlling) as an effort to reconstruct the traditional functions of mosque waqf. The research adopts a case study approach at Masjid Ali-Imron in Kartasura, using descriptive qualitative methods. Data were collected through interviews, observations, and literature reviews. The findings indicate that the POAC approach is effective in designing strategies for utilizing waqf assets, such as building kiosks and providing skills training, to improve community welfare. Implementing this model requires collaboration with Sharia institutions and support from a professional and accountable management system. This study provides practical contributions to waqf managers in enhancing the economic sustainability of the Muslim community through the optimization of productive waqf. Keywords: Mosque waqf, POAC, Economic empowerment, Productive waqf, Waqf management